Top-down structured design techniques - Swann, Gloria Harrington (New York : Petrocelli Books Inc., 1978)
Systems development process is a complex process with a number of phases and tasks as discussed in the book.
"A Petrocelli book."
Includes index.
Includes bibliographical references: p. 137.
II 15/01/2019
Loans
Keywords: Structured programming